Cost Effectiveness Analysis Between Hemodialysis and Peritoneal Dialysis - Novelia, Elsa; Nugraha, Ryan Rachmad; Thabrany, Hasbullah (Jurnal Ekonomi Kesehatan Indonesia, 2017)
The number of patients with End Stage Renal Disease (ESRD) in Indonesia is growing. Increasing prevalence of hypertension and diabetes mellitus contributes to higher prevalence of ESRD. The majority of patients (94%) with ESRD are undertaking hemodialysis (HD) at public and private hospitals. However, continuous ambulatory Peritoneal Dialysis (PD) has been prescribed to small portion of patients with ESRD. The aim of this study was to examine the cost effectiveness between HD and PD on ESRD patients. This study compared 78 HD patients at Hospital X in Bogor and 10 PD patients at Hospital Y in Jakarta. Patient’s quality of life (QoL) was measured using SF 36 questionnaires. The costs were measured by direct medical costs using CBGs prices, direct non-medical costs (transportation, food for patient and family), and indirect medical costs (opportunity costs). The study found that the HD cost per year per patient was IDR 133.4 million and the comparative cost for PD was IDR 81.7 million. The study found lower QoL of HD patients (46.2%) compared to QoL of PD patients (90%). In addition, PD patients had significant better quality of physical activities, emotional states, social function, and sanity. The study found the incremental costs for to HD to reach similar emotional states was IDR 2.0 million compared to PD and IDR 1.8 million for extra physical role gained. It is concluded that PD was more cost-effective than HD in achieving a certain level of quality of life among patients with ESRD in two hospitals in Indonesia.